IN DAYS TO COME : A NEW HOPE FOR ISRAEL - Burg, Avraham; Greenberg, Joel (New York : Nation Books, 2017)
The unorthodox former speaker of the Knesset offers a his clear-eyed assessment of Zionism's failings and what the future holds for Israel and for Judaism
Keywords: Burg, Avraham; Political activists -- Israel -- Biography; Authors, Israeli -- Biography